2021
DOI: 10.3389/fpubh.2021.570098
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Epidemiological and Clinical Characteristics of COVID-19 in Northwest Mexico and the Relationship Between the Influenza Vaccine and the Survival of Infected Patients

Abstract: The first cases of unexplained pneumonia were reported in Wuhan, China, in December of 2019. Later, a novel coronavirus (SARS-CoV-2) was identified as the causal agent of pneumonia. This virus has since spread to more than 180 countries and has been declared a pandemic by the World Health Organization. Herein, we aimed to determine the epidemiological and clinical characteristics of symptomatic patients with coronavirus disease 2019 (COVID-19) and the relationship between the influenza vaccine with a lower ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
(37 reference statements)
0
9
0
1
Order By: Relevance
“…Since 2019, SARS-CoV-2 has spread around the world and has caused many deaths, but currently, we know that some characteristics in subjects, such as age, sex, and underlying diseases, are important to whether patients develop severe COVID-19 4 , but the information available for pregnant women and their neonates with COVID-19 is very scarce. In this study, we showed that 11.2% of the pregnant women were diagnosed with SARS-CoV-2 by RT-PCR tests and 25%…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since 2019, SARS-CoV-2 has spread around the world and has caused many deaths, but currently, we know that some characteristics in subjects, such as age, sex, and underlying diseases, are important to whether patients develop severe COVID-19 4 , but the information available for pregnant women and their neonates with COVID-19 is very scarce. In this study, we showed that 11.2% of the pregnant women were diagnosed with SARS-CoV-2 by RT-PCR tests and 25%…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, before of apparition of vaccines anti‐COVID‐19 to prevent this disease, options to help to combat the ravages caused by the SARS‐CoV‐2 were needed, and different research have demonstrated that influenza virus and coronavirus share some features, 12 due to similarities between viruses the vaccination against influenza confers some level of protection against SARS‐CoV‐2 due to epitopes cross‐reactivity or common immunological pathways involved and some works demonstrated it, because influenza vaccine have reduced risk of SARS‐CoV‐2 infection, also it has increased the survival rate of infected patients. 4 , 13 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, as part of the occupational health program and in agreement with Mexican Ministry of Health policies, we identified those workers with health conditions of potential risk for severe COVID-19 illness, such as diabetes, obesity, hypertension, cancer, lupus, AIDS, or arthritis, aged ≥60 years old, as well as pregnant women [14][15][16][17]. Therefore, they were isolated in their homes; consequently, they were excluded from this report.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%